Effects of Diets Containing Extruded Linseed and Padina pavonica Algae on Meat Rabbit: Carcass Performance and Meat Quality - Nour Elhouda Fehri; Michela Contò; Marta Castrica; Alda Quattrone; Gianluca Renzi; Sabrina Di Giovanni; Stella Agradi; Daniele Vigo; Gabriele Brecchia; Laura Menchetti; Claudia Maria Balzaretti; Doriana Beqiraj; et al. (Foods)
This study investigated the effects of dietary supplementation with extruded linseed (ELS) and Padina pavonica algae extract (PP) on rabbit carcass and meat quality. Ninety-six rabbit carcasses from two production cycles were analyzed. In the first cycle (C1), rabbits were fed a control diet (1CNT), the same diet supplemented with 5% ELS (1ELS5%), and supplemented with 3.5% ELS and 0.2% PP (1LPP3.5%). In the second cycle (C2), the diets varied in composition and supplementation levels: a different control diet (2CNT), the same diet with 5% ELS (2ELS5%), and with 5% ELS and 0.2% PP (2LPP5%). Meat analyses were performed on Longissimus thoracis et lumborum (LTL) muscle for physical properties and on thigh meat (THM) for proximate composition, vitamin E, coenzyme-Q10, cholesterol, fatty acid profile, and mineral content. No significant differences in LTL physical quality were observed in C1, although LTL was brighter in C2 (p < 0.001). THM in C2 had higher fat content (p < 0.001). Dietary supplementation with ELS and PP extract significantly increased polyunsaturated fatty acids (n-3 PUFAs) and improved the n-6/n-3 ratio (p < 0.001) in rabbit meat, demonstrating their positive impact on meat quality.